Oral-motor function in older people: Exploring new dimensions of frailty - Nogueira, D.; Vieira, A.; Reis, E. (Journal of Oral Rehabilitation, 2023)
Background: Oral-motor performance for speech and swallowing, and verbal fluency repre-sent important domains that can determine frailty thresholds in older people. Objectives: The study aims to explore the association between oral-motor performance and verbal fluency to achieve a comprehensive measurement of the frailty phenotype. Methods and Procedures: An exploratory and inferential cross-sectional study was carried out in two nursing homes and two day-care centers. The study comprised a sample of 95 individuals with a mean age of 83 years. TheOral-Diadochokinesis Test (ODDK), Water Swallow Test (WST), Time of Mastication and Swallowing (TOMASS), Maximum Tongue Pressure, Verbal Fluency, Physical Phenotype and Mini-Mental State Examination (MMSE) were used as measurements variables. Results: The comparison of mean values between the performance of observed and normative values for the target population was shown to be statistically significant for all the measure-ments and between the pre-frail and frail. Conclusions: The results of this study add to the growing body of evidence that oral-motor function for speech and swallowing and verbal fluency are relevant to the diagnosis and man-agement of the frailty condition in older people. The frailty syndrome is more than just the traditionally observed physical function, rather it is a multidimensional construct, where addi-tional dimensions should be considered when evaluating frailty in clinical practice